IMPROVING TEENAGER’S CREATIVITY SKILL OF ART AND CULTURE AND CHARACTER BUILDING OF ISLAMIC JUNIOR HIGH SCHOOL STUDENTS - Sinar, Tengku Silvana; Zein, T. Thirhaya; Sofyan, Rudy; Rozanna, T. Mira (Journal of Community Research and Service, 2019)
Creativity Skill of Art and Culture Program (PKKSB) aims to give a training in dancing, pantun reciting and Malay cultural drama to the Junior High School and Islamic Junior High School students of Sinar Serdang which located in Perbaungan, Serdang Bedagai Regency, North Sumatera. As its name, PKKSB has goals to make the students be able in appreciating traditional culture and local wisdom through Malay dance, pantun reciting and drama. By providing the training, the students now have experiences in expressing, creating, and appreciating the art and publicly performing Cultural Arts  in an event held by the governing boards of Serdang Bedagai Regency. This Cultural Arts Performance is held with the aim of conserving and developing the culture for young generations or wider communities. Keywords : art creativity, culture, local wisdom, character building